2021
DOI: 10.1093/cercor/bhab237
|View full text |Cite
|
Sign up to set email alerts
|

Directed Brain Connectivity Identifies Widespread Functional Network Abnormalities in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder characterized by topological abnormalities in large-scale functional brain networks, which are commonly analyzed using undirected correlations in the activation signals between brain regions. This approach assumes simultaneous activation of brain regions, despite previous evidence showing that brain activation entails causality, with signals being typically generated in one region and then propagated to other ones. To address this limitation, here, we de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 102 publications
5
21
0
Order By: Relevance
“…As the current study employs functional MRI scans that have been acquired with longer repetition times, we evaluate the between-group differences at small delays up to lag of 5, which corresponds to the same temporal scale used in ref. 15. The between-group differences in the clustering coefficient and global efficiency at lag of 3 and are shown in Figure 1B and 1C respectively, whereas the corresponding results for lags 2 and 4 are plotted in Supplementary Fig.…”
Section: Amyloid Deposition Results In Changes Of Functional Segregat...mentioning
confidence: 95%
See 4 more Smart Citations
“…As the current study employs functional MRI scans that have been acquired with longer repetition times, we evaluate the between-group differences at small delays up to lag of 5, which corresponds to the same temporal scale used in ref. 15. The between-group differences in the clustering coefficient and global efficiency at lag of 3 and are shown in Figure 1B and 1C respectively, whereas the corresponding results for lags 2 and 4 are plotted in Supplementary Fig.…”
Section: Amyloid Deposition Results In Changes Of Functional Segregat...mentioning
confidence: 95%
“…properties of the network. We have previously shown that the changes in directed functional connectivity due to neurodegenerative processes can be captured by small temporal lags, up to the lag of 7 15 . As the current study employs functional MRI scans that have been acquired with longer repetition times, we evaluate the between-group differences at small delays up to lag of 5, which corresponds to the same temporal scale used in ref.…”
Section: Amyloid Deposition Results In Changes Of Functional Segregat...mentioning
confidence: 99%
See 3 more Smart Citations